Membangun Branding dan Digitalisasi Marketing Rumah Rajut di Sidokare Kecamatan Sidoarjo Kabupaten Sidoarjo: Membangun Branding dan Digitalisasi Marketing Rumah Rajut - Dian Fahriani Dian Fahriani; Muhafidzah Novie; Untung Usada (Universitas Nahdlatul Ulama Sidoarjo, 2022)
. Knitting house owners are small business actors who produce a variety of knittedproducts, such as knitting shoes, bags, clothes, accessories and accessories, and knittingHome Décor. Yuni Suwanti Asih's dedication and persistence in making knitted productsmade her team a partner in PKMS activities. Some aspects of the problems that get priorityfor partners are aspects of production, human resource competence, and aspects of productmarketing. Marketing utilizes social media to introduce products and actively participatesin exhibitions held by the regional government of Sidoarjo Regency. Partner activities arecarried out in a room that is attached to their place of residence and assisted by 4 employeeswho are residents around their production site. Partner turnover ranges from 2-2.5 millionevery month. The approach offered is training and workshops to increase the ability andquality of online marketing human resources, repair/engineering production equipment, andprocurement of production equipment. Assistance is carried out to evaluate this activity.Production time in fulfilling consumer orders and effectiveness in carrying out broaderdesigns and marketing is the expected output target. Partners can save costs by 25% fromusual production and production time efficiency of 20% from the usual time. Productioncosts can also be cut by 15% and production time can also be reduced by up to 20%.Keywords: knitting shoes, online marketing, umkm